Cerebral Microbleeds Were Related With Poor Cognitive Performances on the Dual Task Condition in Older Adults - Li, Xuanting; Yang, Shuna; Qin, Wei; Yang, Lei; Li, Yue; Hou, Yutong; Huang, Qixin; Hu, Wenli (Frontiers in Aging Neuroscience, 2022)
Background: The dual task (DT) was commonly used to assess the risk of falls in older adults and patients with neurological disorders. However, the performance on DT conditions has not been well investigated in patients with cerebral microbleed (CMB). This study is aimed to compare the performance in DT tests between older adults with and without CMB, and to explore the association between CMB and cognitive performances of DT. Methods: This is a cross-sectional study. A total of 211 old adults participated, involving 68 CMB patients. The task protocol involved two global cognition tests, two single cognitive tests (serial 7 subtraction and semantic fluency), two single motor tasks [8-m walking and timed up and go test (TUG)], and three DT tests [walking and serial subtraction (WSS), walking and semantic fluency (WSF), and TUG and serial subtraction (TUGSS)]. The time taken to complete each task and the number of correct responses were recorded. For each DT condition, the correct response rate (CRR) and the dual-task effect (DTE) for the correct number were calculated. Results: Compared with subjects without CMB, CMB patients had worse cognitive performances on DT condition in CRR of WSS (p = 0.003), WSF (p = 0.030) and TUGSS (p = 0.006), and DTE of WSS (p = 0.017). Binary logistic regression analysis showed that the presence of CMB was an independent risk factor for the impairment group for CRR of TUGSS (OR, 2.54; 95%CI, 1.11-5.82; p = 0.027) with the adjustment for confounders, rather than CRR of WSS and WSF, or DTE of WSS. Multiple linear regression analysis showed that CRR of TUGSS decreased with the increase of CMB number grades (β, -0.144; 95%CI, -0.027, -0.002; p = 0.028). Conclusion: The present study indicated that CMBs were closely associated with poor cognitive performances on DT in the elderly. Strongest effect size was seen for CRR of TUGSS, where performance deficits increased in proportion to the degree of CMB burden.